2004
DOI: 10.1074/jbc.m405481200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JNK2 Disrupts Anaphase and Produces Aneuploidy in Mammalian Cells

Abstract: The JNK family members JNK1 and JNK2 regulate tumor growth and are essential for transformation by oncogenes such as constitutively activated Ras. The mechanisms downstream of JNK that regulate cell cycle progression and transformation are unclear. Here we show that inhibition of JNK2, but not JNK1, with either a dominant-negative mutant, a pharmacological inhibitor, or RNA interference caused an accumulation of mammalian cells with 4N DNA content. When observed by immunofluorescence, these cells progressed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
2
28
1
1
Order By: Relevance
“…Besides the clear effects we demonstrated for the kinesin-1/JNK pathway in interphase cells, its role in mitosis would also be worth studying. Indeed, although kinesin-1 knockdown was not found to produce an obvious defective mitotic phenotype (39,40), JNK basal activity is required to allow mitotic progression and correct anaphase (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the clear effects we demonstrated for the kinesin-1/JNK pathway in interphase cells, its role in mitosis would also be worth studying. Indeed, although kinesin-1 knockdown was not found to produce an obvious defective mitotic phenotype (39,40), JNK basal activity is required to allow mitotic progression and correct anaphase (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…75 In several cellular models reduction of JNK1 and JNK2 levels or activity results in S phase accumulation. [76][77][78][79] The role of JNK in the G 2 phase of the cell-cycle is documented by RNA interference and the use of the specific JNK inhibitor SP600125. In both cases, cell treatment induces an accumulation of cells with 4N DNA content.…”
Section: Jnk1 and Jnk2 In Cell Cycle Regulationmentioning
confidence: 99%
“…Depending on the particular cell type, cell-cycle arrest is accompanied by increasing DNA accumulation or by cell death. 16,76,77 This mechanism may be responsible for the anti-cancer activity of several natural compounds with anti-JNK activity. 80,81 Interestingly, mouse embryonic fibroblasts derived from JNK1 -/-and JNK2 -/-mice revealed that these two kinases have somewhat different roles in cell cycle regulation: JNK2 -/-cells exhibit a shorter G 1 cell cycle phase, i.e., they enter S phase earlier than wild-type counterparts, while JNK1 -/-cells show the inverse phenotype, a longer G 1 phase than wild-type cells.…”
Section: Jnk1 and Jnk2 In Cell Cycle Regulationmentioning
confidence: 99%
“…In addition to increased proliferation due to lack of JNK2, a recent report also suggested that specific inhibition of JNK2 resulted in aneuploidy in human cells. 25 This was proposed to be due to defects in chromosome segregation and central spindle formation during anaphase, which eventually resulted in polyploidy. Together, the emerging trend points to increased proliferation in multiple cell types in the absence of JNK2 (Table 1).…”
Section: Jnk2 Negatively Regulates Proliferation Of Hepatocytes and Kmentioning
confidence: 99%